Computer acquisition and analysis of insect feeding monitor data - Noyes, S.; Margolies, D.C.; Reese, J.C.; Dixon, A.; Bramel-Cox, P.J. (Oxford University Press, 1990)
Electronic insect-feeding monitors are increasingly being used to study the feeding behavior of piercing-sucking insects in relation to host resistance and biotypes. The original AC design has been modified several times to simplify and expand the signal generator and signal processor. We report a method to improve the monitoring stage by using an MS-DOS computer to replace strip chart recorders. We present fragments of custom software in BASIC, C, and 8086 assembly language designed to simplify the collection and analysis of data. The analysis software allows a full range of operations to be performed on the data, including signal identification, frequency domain analysis, and filtering. We offer suggestions on integrating these fragments into customized software for different computer systems. An example using greenbugs, Schizaphis graminum (Rondani), on sorghums demonstrates that collection and analysis of feeding monitor data with the computer system is as accurate, faster, and less expensive than previously used systems.